Acrolein genotoxicity in Drosophila melanogaster. - Sierra, L.M.; Barros, A.R.; Garcia, M.; Ferreiro, J.A.; Comendador, M.A. (Mutation Research, 1991)
The genotoxicity of acrolein in D. melanogaster was investigated using 2 different SMART assays, the eye spot and wing spot tests, and 2 germinal tests, the sex-linked recessive lethal (SLRLT) and sex chromosome loss (SCLT) tests. For the 2 latter, exposure by feeding as well as injection was used. The results indicate that: (i) acrolein is mutagenic in the SLRLT when injected but not when fed; (ii) the SCLT did not reveal clastogenic effects; (iii) acrolein had genotoxic effects in both SMART assays; (iv) we also had several indications that acrolein is metabolized into a second genotoxic product.